A New Look at an Inscribed Ceramic Medallion with Gladiators (Equites) from the Region of Parthicopolis in the Roman Province of Macedonia - Nankov, Emil (Tekmeria, 2021)
This paper reconsiders a ceramic medallion found near the village of Palat on the right bank of the Strymon River, ca. 8 km northwest of the town of Sandanski in southwest Bulgaria. The cluster of Roman settlements near the village of Palat may have belonged to the territory of Parthicopolis (mod. Sandanski), which fell under the jurisdiction of Macedonia Prima. The medallion illustrates a gladiatorial combat between two equites, who are identifiable through their pairing, clothing and weapons. Autopsy established the presence of a Greek inscription, which had so far escaped attention. The recorded names, Σωτηρίδας and Αἴας, seem to correspond to the equites depicted. Gladiatorial scenes with inscribed names are quite commonly represented on various media, including ceramic medallions, especially in the western provinces of the Roman empire. Ceramic medallions, serving a range of functions, were mass-produced in molds. The larger dimensions of our example, most probably a product of a local workshop, could be intended to be hung on a wall in the privacy of a domestic residence, although the possibility for funerary use cannot be excluded. This artifact from Palat, inspired by imagery current in the western provinces of the Roman empire, bears testimony to Roman cultural influence in the territory of Parthicopolis in the first half of the third century AD. At the same time, it offers hitherto overlooked iconographic indications that the equites’ role in the games was commemorated through the medium of ceramic medallions along the Thracian frontier, as it was in the western provinces of the Roman empire.